The generation of wealth in the travel agencies located in the regions of Arequipa, Cusco, Lambayeque and La Libertad, year 2013 and the contribution to the regional gross domestic product - Marsano Delgado, José Manuel Enrique (2017)
Describes the research carried out by the Observatory Tourist of Peru of the Professional School of Tourism and Hospitality of the University of San Martin de Porres, who poses as an aim to see the generation of the gross domestic product (GDP) of the travel agencies in the regions of Arequipa, Cusco, Lambayeque and La Libertad; as well as its contribution to the GDP of each region. The methodology used was exploratory, transverse, descriptive and hermeneutic. We gave a quantitative approach, where applied techniques of accounting and economic research of the satellite accounts. The documentary and technical field technique were used. The universe was made up of 100 % of the travel agencies in the regions of Arequipa, Cusco, Lambayeque and La Libertad. The surveys were applied to executives and heads of establishments.